2017
DOI: 10.1371/journal.pone.0174349
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorus stress on Microcystis aeruginosa growth and phosphorus uptake

Abstract: This study was designed to advance understanding of phosphorus regulation of Microcystis aeruginosa growth, phosphorus uptake and storage in changing phosphorus (P) conditions as would occur in lakes. We hypothesized that Microcystis growth and nutrient uptake would fit classic models by Monod, Droop, and Michaelis-Menten in these changing conditions. Microcystis grown in luxury nutrient concentrations was transferred to treatments with phosphorus concentrations ranging from 0–256 μg P∙L-1 and luxury nitrogen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Therefore, chemical P fertilizers are used to overcome this deficiency, but immobilization and runoff make it unavailable for successful crop production [12]. Besides, this injudicious use of P fertilizers leads to environmental pollution and increases the cost of production [13]. Moreover, the naturally available reservoirs of rock phosphate are depleting day by day due to its overuse and prices are rising as the resource becomes scarcer [14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, chemical P fertilizers are used to overcome this deficiency, but immobilization and runoff make it unavailable for successful crop production [12]. Besides, this injudicious use of P fertilizers leads to environmental pollution and increases the cost of production [13]. Moreover, the naturally available reservoirs of rock phosphate are depleting day by day due to its overuse and prices are rising as the resource becomes scarcer [14].…”
Section: Introductionmentioning
confidence: 99%
“…High pH and higher concentration of CaCO 3 are responsible for P unavailability in alkaline calcareous soils [ 2 4 ] while in acidic soils, higher concentration of Al and Fe declines P availability to plants [ 5 , 6 ]. Moreover, continuously increasing prices, injudicious use of N fertilizers and increased environmental issues of phosphoric fertilizers [ 7 ] aggravate the situation manifold and are among the major reasons of low P application in crop production system [ 1 , 8 ]. Rock phosphate ores may get depleted in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…Microcystis aeruginosa grows slowly when the chlorophyll-a content has basically no change in the initial stage of culture (about one week), this stage can be considered as lag phase. Some studies have suggested that the growth rate of Microcystis mainly depends on the intracellular phosphorus [24], not extracellular phosphorus, which can be confirmed from the lag phase. Microcystis aeruginosa did not quickly enter the logarithmic phase despite the high phosphorus content of water from phosphorus-deficient state that has come into the phosphorus-rich medium, which can indicate that Microcystis was quickly uptaking the extracellular phosphorus in this phase in preparation for its massive proliferation.…”
Section: Growth Of Microcystis Aeruginosa Fachb-905 and Fachb-469 Undmentioning
confidence: 98%